Catalytic Asymmetric Amino Acid and Its Derivatives by Chiral Aldehyde Catalysis - Lin, Kaijin; Shi, Ang; Shi, Chunhong; Lin, Jinbiao; Lin, Honggui (Frontiers in Chemistry, 2021)
Amine acid transformation is an important chemical process in biological systems. As a well-developed and acknowledged tool, chiral aldehyde catalysis provides good catalytic activation and stereoselective control abilities in the asymmetric reaction of N-unprotected amino acid esters and amino acid esters analogues. In which, the key to success was the design of the catalysts derived from chiral BINOL aldehyde, which based on face control of the enolate intermediates. In this review, one of the co-catalytic system that combined with a transition metal to form a multiplex catalytic system and the well-established multiplex stereocentres of chiral aldehyde catalysis have been reviewed. Finally, the novel organocatalysis are prospected.